Influence of Technology Infrastructure on Quality of Learning in Public Primary Schools Nyeri County, Kenya - Nyaga Maina John; Kimosop Maurice; Gachahi Wambugu Michael (African Journal of Education,Science and Technology (AJEST), 2025)
Provision of free primary education by the Kenyan government has been successful with regard to increased enrolment in public schools. However, a big concern has been on the quality education which is often seen in how pupils perform. The purpose of the study was to establish influence of technology infrastructure on quality of learning in public primary schools in Nyeri County, Kenya. The study was guided by the Multimedia learning theory and Diffusion of Innovation Theory. The study employed a descriptive research design. The target population for this study was 382 public primary schools in Nyeri County. The target respondents were the 382 head teachers and 3850 teachers. The study used simple random sampling and stratified random sampling. The study used Krejcie and Morgan (1970) Table to determine samples size and arrived at 38 head teachers and 362 teachers. This study used questionnaires to collect data from teachers and interview guides to collect data from head teachers. The quantitative data was analyzed using Statistical Package for Social Sciences (SPSS 28) software. The study used descriptive and inferential statistics. Qualitative data derived from interview guides was analyzed using content analysis. Findings were presented in tables. Findings show that there is a strong significant relationship between technology infrastructure and quality of learning in public primary schools in Nyeri County (r=0.541, p=0.000). The recommendations are; The ministry of education should ensure affordable, dependable, and easily accessible internet connectivity in all public schools, and school administrators should look for government funding to construct and furnish computer labs as well as buy additional Information Communication Technology equipment like scanners, photocopiers, and printers.